2018
DOI: 10.1038/s41598-018-29339-0
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic germ cell extracts erase imprinted genes and improve the efficiency of induced pluripotent stem cells

Abstract: Patient-specific induced pluripotent stem cells (iPSCs) have the potential to be useful in the treatment of human diseases. While prior studies have reported multiple methods to generate iPSCs, DNA methylation continues to limit the totipotency and reprogramming efficiency of iPSCs. Here, we first show the competency of embryonic germ cells (EGCs) as a reprogramming catalyst capable of effectively promoting reprogramming induced by four defined factors, including Oct4, Sox2, Klf4 and c-Myc. Combining EGC extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 50 publications
1
6
0
Order By: Relevance
“…mediated by cell-secreted factors 10,16,17 . Consistently with this hypothesis, we recently reported that the efficiency of reprogramming of human somatic cells to hiPSCs can be dramatically improved in a microfluidic confined environment 18 , which enhances the accumulation of secreted factors 19,20 and sustains the acquisition of both primed 18,21 and naïve human pluripotency 22 .…”
Section: Introductionsupporting
confidence: 57%
See 1 more Smart Citation
“…mediated by cell-secreted factors 10,16,17 . Consistently with this hypothesis, we recently reported that the efficiency of reprogramming of human somatic cells to hiPSCs can be dramatically improved in a microfluidic confined environment 18 , which enhances the accumulation of secreted factors 19,20 and sustains the acquisition of both primed 18,21 and naïve human pluripotency 22 .…”
Section: Introductionsupporting
confidence: 57%
“…Secretome analysis during reprogramming. To investigate the dynamic changes of cell-secreted proteins during reprogramming of human fibroblasts, tandem mass spectrometry (LC-MS/MS) was performed on conditioned media pooled from microfluidic channels every 2 days [19][20][21] (Fig. 1B).…”
Section: Resultsmentioning
confidence: 99%
“…OCT-3/4 is regulated by PTM processes that are involved in phosphorylation [33,34], SUMOylation [35], ubiquitination [1,36,37], glycosylation [38], methylation [39][40][41], and acetylation [42] (Figure 2).…”
Section: Oct-3/4 Regulated By Several Ptmsmentioning
confidence: 99%
“…proposed that combining three transcription factors, NANOG, OCT-3/4, and TET1, regulates DNA methylation modification, which governs pluripotency through reprogramming [39]. Differentiation-induced de novo DNA demethylation can repress pluripotency genes including OCT-3/4, whereas active DNA demethylation reactivates pluripotency genes [41].…”
Section: Oct-3/4 Regulated By Several Ptmsmentioning
confidence: 99%
“…3/ Treating permeabilized cells with cell extracts from pluripotent cells – Permeabilized differentiated cells are partially reprogrammed when exposed to protein extracts prepared from pluripotent (ESC) cells or germ cells [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%